Land Use Land Cover Change Analysis Using Multi Spatial Data For Sungai Raya Catchment - Sopian, Mohd Idzadin Mohd (2014)
Water resources are one of the critical importance’s in human life. The rapid development, population growth, migration and urbanization cause water crisis, in quantity and quality. Sungai Raya catchment is catchment in Perak state. Catchment area is located at the edge of the Ipoh city and part of it is included in the Ipoh Plan 2020. In controlling the suburbanisation process while securing water resource, officials of legislators, planners, state and local governmental required Land Use Land Cover (LULC) information in determining the suitable policy. The temporal Land Use Land Cover (LULC) change analysis for Sungai Raya watershed evaluation is conducted from 1990 to 2010, by integrating Digital Elevation Model (DEM), satellite dataset and Geographic Information System (GIS). Study conducted utilizing post-classification comparison and GIS approach, with network detection, pixel base classification and object base classification technique.